2006
DOI: 10.1021/ie0514509
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Solid Polycyclic Aromatic Hydrocarbons in Pressurized Hot Water:  Correlation with Pure Component Properties

Abstract: A semiempirical relationship was developed to correlate solubility of solid polycyclic aromatic hydrocarbons (PAHs) in pressurized hot water using only pure-component properties. The required properties of water include cohesive energy density, internal pressure, and relative permittivity (dielectric constant), all at the particular temperature and pressure. The required properties of PAHs include triple-point temperature, enthalpy of fusion, the molar volume of the subcooled liquid, and the molar volume of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 59 publications
2
55
0
Order By: Relevance
“…8.4 Activity coefficients of oxygenated aromatic solutes in saturated aqueous solutions: ○, xanthene; Â, anthrone; e, xanthone; *, thioxanthone; Δ, 9,10-anthraquinone. Anthracene (Karásek et al 2006b) r is shown for reference. The lines serve just to guide the eye.…”
Section: Subcritical Water As An Extraction Agent: Pros and Consmentioning
confidence: 99%
“…8.4 Activity coefficients of oxygenated aromatic solutes in saturated aqueous solutions: ○, xanthene; Â, anthrone; e, xanthone; *, thioxanthone; Δ, 9,10-anthraquinone. Anthracene (Karásek et al 2006b) r is shown for reference. The lines serve just to guide the eye.…”
Section: Subcritical Water As An Extraction Agent: Pros and Consmentioning
confidence: 99%
“…In recent years, many efforts have been made to develop semi-empirical approaches [10][11][12][13] to correlate the solubility *Address correspondence to this author at the Instituto de Investigación en Ciencias de la Alimentación CIAL (CSIC-UAM) C/Nicolás Cabrera 9, Universidad Autónoma de Madrid, 28049 Madrid, Spain; Tel: +34910017927; Fax: +34910017900; E-mail: tiziana.fornari@uam.es of solids in HPW, based on the use of solute and solvent (water) physical properties. For example, Miller et al [10] developed a simple equation to relate the effect of increasing temperature on the solubility of polycyclic aromatic hydrocarbons (PAHs) in liquid water at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Another semi-empirical relationship, presented by Karásek et al [13], uses the temperature dependency of pure water physical properties (internal pressure, cohesive energy density and dielectric constant) to correlate the activity coefficients of PAHs in water as a function of temperature. Pure solute physical properties (fusion enthalpy, triple-point temperature, subcooled liquid molar and solid molar volumes) are employed to calculate the ratio of the solute fugacity in the solid and subcooled liquid states, and high degree of correlation of the experimental solubility data was achieved [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations